A STUDY OF HUMAN SKILL ACHIEVEMENT IN MALAYSIAN PUBLIC UNIVERSITIES: KNOWLEDGE, SKILL AND ATTITUDE - Ngadiman, M. Y.; Hussin, B.; Abdul Majid, I. (2011)
The principle of sustainable technical skill development is an integrated skill approach in the long terms by the instruments of science, technologies, economics and global considerations. The prospect of full implemented successfully needs a workforce which is equipped with sustainable development with related knowledge, skill and attitude (KSA). This study is related to the human skill achievement referred to the capability of technical staff in public universities. Purposely is to establish the procedures for the management and control of capital equipment. It also is to satisfy the requirements of the federal and state government and good business practices respecting control over the capital equipments. This study will be a significant endeavor for Human Resource Development (HRD) to measure the capability of human factors through KSA. The methodology of this descriptive study by searching the related topic literatures, white papers, technical papers, conference proceedings, and web-pages or even communicate to the personnel in selected public universities in Malaysia. The finding of this study will contribute to develop Overall Equipment Efficiency Model (OEEM) that could be measurable throughout to the technical skill performance among technicians in the engineering lab derived from KSA components. Therefore, human skill developments are the first competence bench marking in the capital equipment management in Malaysian public universities was identified.